Possibility of detecting meteorites buried within the ice by radio echo sounding - Nishio, Fumihiko; Wada, Makoto; Mae, Shinji (1981)
P(論文) Recovery of large numbers of Yamato meteorites and Allan Hills meteorites in Antarctica led us to postulate the presence of meteorite pieces still buried in the ice. To elucidate the concentration mechanism of a large number of meteorites within a limited region in the bare ice areas, it may be significant if meteorites buried within the ice could be detected. If meteorites buried in the ice are taken out together with the surrounding ice, valuable information on chronological problems of both meteorite and ice will be obtained. A theoretical analysis on the possibility of locating of meteorites buried in the ice by means of radio echo sounding is described in this paper. The radar equation is used to calculate the reflected power from meteorite pieces buried in ice. Assuming that meteorite pieces are spherical in shape and iron meteorites are conductive spheres, we may investigate the problem of the case where reflections from meteorite pieces within the ice are strong enough to be detected with the radio echo sounding apparatus applying the electromagnetic wave of 400 MHz and 80 MHz, taking G_0=2 as the antenna gain, and P_r/P_t=(10)^<-10> as the ratio of the received and transmitted power. As the size distributions of diameter of meteorite pieces are given for the Yamato stony meteorites and the iron meteorites, the relation between the detectable diameter of meteorite pieces and the burial depth in the ice was obtained. It was concluded that the Yamato stony meteorites may be detectable unless the burial depth exceeds 10m. However, most of the Yamato stony meteorites having the maximum frequency of diameter of about 1 cm are probably detectable if they are buried within a depth of 1m. For the iron meteorites, if the diameter is about 20cm, the maximum frequency of diameter in size distribution, they are detectable within the depth of about 50m. departmental bulletin paper